The experiences of autistic medical students in relation to seeking and receiving online support: A phenomenological study - Samantha Cooper; Mary Doherty; Sebastian Charles Keith Shaw (PLoS ONE, 2026)
Background Previous studies have reported that autistic medical students experienced specific challenges throughout their medical studies, including isolation, bullying, and discrimination from their institutions – alongside receiving minimal support. Despite this, it has been argued that many autistic characteristics are well aligned with practising medicine, bringing key benefits to patient care. ‘ Autistic Medical Students’ (AMS) is an online international support group, containing over 200 members – a sub-group of Autistic Doctors International. This study aims to explore the experiences of AMS membership and if membership has any wider impacts on medical studies or wellbeing. Within this, it aims to explore the experiences that led to seeking this support. Methods This was a qualitative study. Five participants from AMS were recruited. Semi-structured, 1:1 interviews were conducted via Zoom. These were audio recorded, transcribed verbatim, and analysed using interpretive phenomenological analysis. Results Group experiential themes included: medical culture, belonging, safety, ability to thrive, internalised optimism for the future, and real modelling. Participants experienced systemic ableism and weaponised professionalism, which led to a sense of helplessness for their futures. AMS had a positive impact on participants. They experienced a sense of belonging, alongside an improved ability to both recognise their own needs and implement accommodations. They also felt better able to advocate for support. ‘Real modelling’ from peers and autistic doctors motivated participants in their wider medical studies. Of particular benefit was that AMS uniquely encompassed both being autistic and a medical student, making its specific support invaluable. Discussion Findings were in keeping with previous research. Autistic peer-to-peer communication enabled development of social relationships and self-identity. Autistic medical students and doctors exhibit traits that make them assets to medicine. This study highlights the need for knowledge, acceptance and representation of autism within medical education – to enable autistic medical students to thrive.